PENGGUNAAN MEDIA YOUTUBE UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI MELALUI AKUN “CATATAN KHOIRUL TRIANN” - Muhammad Faridh Wazdy; Hindun (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
The aims this research are 1) To describe students' poetry writing skills using YouTube media. 2) Knowing students' ability to use YouTube in distance learning, in the pandemic era. The research method used is descriptive qualitative. Documentation techniques in the form of data collection, use of YouTube, and assessment of the practice of writing poetry with the application of YouTube as a medium. The results showed that the majority of students became skilled at writing poetry by building figure of speech, stanzas, and diction. Keywords: Poetry Writing Skills, Pandemic, Youtube